2017
DOI: 10.1007/s10811-017-1343-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomass soaking treatments to reduce potentially undesirable compounds in the edible seaweeds sugar kelp (Saccharina latissima) and winged kelp (Alaria esculenta) and health risk estimation for human consumption

Abstract: Biomass soaking treatments to reduce potentially undesirable compounds in the edible seaweeds sugar kelp (Saccharina latissima) and winged kelp (Alaria esculenta) and health risk estimation for human consumption-Manuscript Draft-Manuscript Number: Full Title: Biomass soaking treatments to reduce potentially undesirable compounds in the edible seaweeds sugar kelp (Saccharina latissima) and winged kelp (Alaria esculenta) and health risk estimation for human consumption Article Type: Original Research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 66 publications
6
41
0
Order By: Relevance
“…Also, Stévant et al. () reported decreased I content of S. latissima , to below 2,000 mg I/kg dw (originally 4,898 mg/kg dw in May 2015 and 6,568 mg/kg dw in June 2015), after a 1 hr soaking treatment in freshwater (32 °C). However, when compared to raw L. digitata , steaming it (5 min, 105 °C) resulted in an increased concentration of I ( p < .05, n = 20; Alves et al., ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, Stévant et al. () reported decreased I content of S. latissima , to below 2,000 mg I/kg dw (originally 4,898 mg/kg dw in May 2015 and 6,568 mg/kg dw in June 2015), after a 1 hr soaking treatment in freshwater (32 °C). However, when compared to raw L. digitata , steaming it (5 min, 105 °C) resulted in an increased concentration of I ( p < .05, n = 20; Alves et al., ).…”
Section: Resultsmentioning
confidence: 98%
“…For example, boiling dried S. latissima in freshwater for 2 min resulted in about a third reduction from an initial value of 380 mg I kg/dw (Lüning & Mortensen, 2015). Also, Stévant et al (2018) reported decreased I content of S. latissima, to below 2,000 mg I/kg dw (originally 4,898 mg/kg dw in May 2015 and 6,568 mg/kg dw in June 2015), after a 1 hr soaking treatment in freshwater (32 • C). However, when compared to raw L. digitata, steaming it (5 min, 105 • C) resulted in an increased concentration of I (p < .05, n = 20; Alves et al, 2018).…”
Section: 123mentioning
confidence: 99%
“…Therefore, some precautions must be taken regarding the consumption of iodine-rich seaweeds although, despite the increasing consumer acceptance, seaweeds are still regarded as an exotic food item in Europe and their consumption is not enough to exceed the recommended levels. In fact, the inclusion of seaweeds in the diet could support current efforts to improve I status among European populations [ 13 ].…”
Section: Mineral Content Of Macroalgaementioning
confidence: 99%
“…An exception is made for France, which is the only European country that has already defined limits of potentially toxic compounds in seaweeds to be used for human consumption. Even though, these are only recommendations from the food safety authority and are not legally binding [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As SPC, SPP will need to be considered a commodity and large-scale production must be investigated to achieve competitiveness. Harvested seaweed decomposes rapidly and therefore must be processed rapidly (Stévant et al 2017b;Stévant et al 2018). In addition, the best areas reported for seaweed farming in Norway are offshore (Broch et al 2019).…”
Section: The Challenges Of Seaweed Farmingmentioning
confidence: 99%